Effects of Irrigation Levels on the Yield of Chickpea (Cicer Arietinum Linn) Due to Incidence of Helicoverpa Armigera (Bangladesh Journal of Botany, 2021)
Effects of four different irrigation levels viz., One irrigation at 50 per cent flowering stage, one irrigation at grain filling/pod initiation stage, two irrigations (one at 50 per cent flowering + one at grain filling stage), control (without irrigation) on the incidence of gram pod borer, Helicoverpa armigera (Hubner) on chickpea were studied during Rabi, 2014-15 and 2015-16 at Research Farm, College of Agriculture, Bikaner (Rajasthan), India. Results revealed that the highest mean larval population (3.12 larvae per 5 plants) and maximum pod damage (33.24%) were recorded in the crop which was irrigated twice viz., one at 50 per cent flowering stage and second at grain filling stage. The lowest larval population (2.03 larvae per 5 plants) with minimum pod damage (8.34%) was recorded in the crop where irrigation was not given. The maximum seed yield (11.05 q/ha) was obtained from the crop which was irrigated two times and minimum seed yield (7.56 q/ha) was obtained in control.Bangladesh J. Bot. 50(4): 1203-1207, 2021 (December)